Pengaruh Literasi Digital Terhadap Psikologi Anak Sekolah Dasar - Khairin Revalia Ramadhani; Adrias Adrias; Aissy Putri Zulkarnaini (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital literacy plays an important role in the psychological development of elementary school children, both from cognitive, social, and emotional aspects. This study aims to analyze the influence of digital literacy on child psychology by highlighting the positive and negative impacts it causes. The research method used is a literature review with reference to various previous studies on digital literacy and its development in children. The results of the study show that digital literacy can improve critical thinking skills, creativity, and expand children's social interactions. In addition, access to technology can also help children understand the world more broadly and increase empathy for social issues. However, excessive use of digital technology without adequate supervision can have negative impacts, such as addiction to gadgets, decreased social interaction, and impaired concentration in learning. Exposure to age-inappropriate content and the risk of cyberbullying are also threats to children's mental health. Therefore, an active role of parents, educators, and policymakers is needed in supervising and guiding children in using digital technology wisely. This study confirms that digital literacy has a complex impact on child psychology. With proper guidance and supervision, the benefits of digital literacy can be optimized, while the negative impact can be minimized. Therefore, a balanced approach in the application of digital literacy is needed to support the optimal development of children's psychology.